The Measurement of Service Quality at Linow Lake Tourist Attraction Using Servqual Method - Stefani I. Angmalisang (AIBPM Publisher, 2021)
The tourism industry sector in North Sulawesi is currently getting more attention by the government. Linow lake is one of the busiest and visited tourist attraction. The tourism industry must apply the concepts, regulations and guidelines in tourism development in order to be able to maintain and increase the number of tourist visits which will lead to economic benefits for the tourism industry and local communities. In Tomohon city itself, there are so many natural tourist attractions which as beautiful as Linow Lake. In order for tourists to feel satisfied and want to visit the Linow lake on the next day, the quality of service cannot be overlooked. For this reason, measurement of service quality was carried out using five dimensions, Tangible, Reliability, Assurance, Responsiveness, and Empathy. It will be measured to 100 respondents, how the expectations and perceptions of tourists about the service quality at Linow Lake tourist attractions. Measurements were carried out by using servqual method, which calculates the difference between the expectations and perceptions of tourists consisting of 22 questions. The result of the analysis showed a positive value of 0.17, which means that the service quality at Linow Lake tourist attractions has exceeded the expectations of visitors. However, one dimension, responsiveness, gets a negative value, and it is expected that the management can improve the quality of its services in terms of response speed, especially on busy visitor days.